A new brachymetopid trilobite from the Early Permian Shakhtau reef complex of the southwestern Urals, Bashkortostan, Russia - Mychko, Eduard V.; Savchuk, Oles V. (Zootaxa, 2019)
New specimens of trilobites from the Lower Permian limestone reef Shakhtau (Sterlitamak, Bashkortostan, Russia) are described as Brachymetopus (Conimetopus) alekseevi Mychko, sp. nov. Although represented by a limited number of specimens, the new species is significant in extending the stratigraphic distribution of the subgenus Brachymetopus (Conimetopus) Hahn and Hahn, 1985, whose members were previously known exclusively from Carboniferous deposits. Material described previously from the Early Permian (Asselian) of the Chelyabinsk Region is also assigned to the new species.